Navigating the Body Multiple: Biomedicine, Genetics, and Sex/Gender in the Lives of CAH Patients. Issue 1 (1st March 2020) - Krishnamurthy, Mathangi
Abstract: In this article, the author is interested in understanding how forms of care deployed for people with congenital adrenal hyperplasia (CAH) engage with ambiguously sexed bodies. CAH is a collection of inherited genetic conditions affecting the adrenal glands that in its classic form clinically manifests itself by way of atypical genitalia in newborn infants. It is mainly seen in females, but also in males, and often results in surgical intervention to produce a more typically sexed appearance. In this article, the author traces the ways in which genetic technologies, in cohort with clinical diagnoses and consultation sessions between geneticists, general practitioners, endocrinologists, surgeons, psychiatrists, and parents, assign sex to CAH patients and evaluate normality and abnormality vis-à-vis sexuality and gender. This project locates itself at the interstices of, on the one hand, surgical and other interventions suggested for the body to conform to genetic certainty in relation to sex, and, on the other hand, a range of cultural contexts, norms, and consequences. The author investigates how different forms of biomedicine help practitioners produce care regimes in response to the specific local, gendered, cultural, and class contexts of the CAH patient, and very specifically asks how these may or may not push the boundaries of a sex/gender binary. In the process, the author also speculates on the gendered futures available for CAH bodies.